2016
DOI: 10.1016/j.jdiacomp.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Associations between recent severe hypoglycemia, retinal vessel diameters, and cognition in adults with type 1 diabetes

Abstract: Aims Mild cognitive dysfunction has been identified in children and adults with type 1 diabetes, but most studies have failed to find a relationship between severe hypoglycemia and cognition, despite reports of such associations in older adults with type 2 diabetes. Focusing on older adults with type 1 diabetes, we examined associations between cognitive performance and recent episodes of severe hypoglycemia, retinal vessel diameters and the presence of micro- and macrovascular complications. Methods Cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
6
31
0
5
Order By: Relevance
“…These results are consistent with CRAE measures, but not CRVE measures, being associated with microvascular complications in an earlier study of middle-aged Danish T1D patients 39 and with cognitive performance in T1D participants of the Wisconsin Epidemiologic Study of Diabetes Retinopathy. 6 We also replicated results of the Beaver Dam Eye Study showing CRVE was related to older age in our T1D participants. 40 The reasons for these disparate relationships between CRAE and CRVE are not known and deserve further study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results are consistent with CRAE measures, but not CRVE measures, being associated with microvascular complications in an earlier study of middle-aged Danish T1D patients 39 and with cognitive performance in T1D participants of the Wisconsin Epidemiologic Study of Diabetes Retinopathy. 6 We also replicated results of the Beaver Dam Eye Study showing CRVE was related to older age in our T1D participants. 40 The reasons for these disparate relationships between CRAE and CRVE are not known and deserve further study.…”
Section: Discussionsupporting
confidence: 85%
“…5 The Wisconsin Epidemiologic Study of Diabetic Retinopathy recently reported a cross-sectional association between retinal vascular measures and CI in adults with T1D. 6 Whether longitudinal changes in these retinal vascular measures (e.g. narrowing or widening over time) could be detectable prior to the onset of CI in adults with T1D remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent SH (<1 year) reduced mental efficiency and executive functioning in older people (mean age 55 years) with a long duration of childhood-onset disease. 43 Of the 14 cross-sectional studies, 6 did not find an association between SH and CD but recruited at an older mean age (3/6 recruited at ⩾25 years) and had in general lower thresholds for defining hypoglycaemia as discussed earlier. 19,18,27,34,39,42 Thus, studies that recruited younger participants and defined SH as more severe manifestations of hypoglycaemia were more likely to find a significant association with CD…”
Section: Prospective Cohort Studiesmentioning
confidence: 93%
“…SH in the older age group was associated with larger deficits in overall cognition and cognitiveprocessing speed (effect size 6.6 SD). 43,54,56,57 Strengths and limitations The strengths of this study include the use of a multidatabase search culminating in the summary of 62 relevant articles. To the best of our knowledge, this is the first systematic review focusing specifically on the relation between hypoglycaemia and CF in type 1 diabetes across all age groups and thus providing an in-depth review of this topic.…”
Section: Cognitive Domains Affected By Prior Exposure To Shmentioning
confidence: 99%
“…A recent cross-sectional study in older people with type 1 diabetes confirmed that hypoglycaemia, in addition to preexisting microangiopathy was associated with cognitive decrements [23]. The role of hypoglycaemia in type 1…”
Section: Late Adulthoodmentioning
confidence: 94%